2021
DOI: 10.1007/s11786-021-00507-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of Indo-European Language Families via an Algebro-Geometric Analysis of Their Syntactic Structures

Abstract: Using Phylogenetic Algebraic Geometry, we analyze computationally the phylogenetic tree of subfamilies of the Indo-European language family, using data of syntactic structures. The two main sources of syntactic data are the SSWL database and Longobardi's recent data of syntactic parameters. We compute phylogenetic invariants and estimates of the Euclidean distance functions for two sets of Germanic languages, a set of Romance languages, a set of Slavic languages and a set of early Indo-European languages, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 37 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…With Slovenian excluded, all three Longobardi et al (2013); Shu et al (2017); Nurbakova et al (2013) agree on this tree. The reconstruction is robust: with approximately 60% of the parameters sampled uniformly randomly, this topology appears with a probability in excess of 0.6.…”
Section: Slavic Languagesmentioning
confidence: 77%
See 3 more Smart Citations
“…With Slovenian excluded, all three Longobardi et al (2013); Shu et al (2017); Nurbakova et al (2013) agree on this tree. The reconstruction is robust: with approximately 60% of the parameters sampled uniformly randomly, this topology appears with a probability in excess of 0.6.…”
Section: Slavic Languagesmentioning
confidence: 77%
“…Such phenomena are beyond what is describable purely in terms of Markov models on trees. Moreover, different syntactic parameters are not independent variables: some relations are explicitly known (as discussed in Longobardi and Guardiano (2009), Longobardi (2017a) for instance), while other relations can be detected through methods of data analysis, as in Ortegaray et al (2018), Park et al (2017), or through methods of coding theory Shu and Marcolli (2017), Marcolli (2016). The presence of dependencies between syntactic parameters violates the Markov models on trees hypothesis that these variables can be treated as identically distributed independent random variables.…”
Section: The Influence Of Sites In Leaf Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The same method was re-used in (Longobardi et al, 2013), which was concluded in a similar way. In a recent work, Shu et al (2021) applied a different comparison technique on the same syntactic characteristics, using Markov models. In all of those works, the selection of the syntactic characteristics to be used for comparison, plays an important role in the creation of a language proximity model.…”
Section: Related Workmentioning
confidence: 99%